Association Between Immune-Inflammation Index (SII) and Ferritin with Hepatic Function in Patients with Thalassemia Major - Titis Yoga Safitri; I Edward Kurnia Setiawan L; Nahwa Arkhaesi; Nyoman Suci Widyastiti (Jurnal Kedokteran Diponegoro (Diponegoro Medical Journal), 2024)
Background: Thalassemia major is associated with ferritin levels and SII values with impaired liver function. Furthermore, the measurement of impaired liver function is carried out using Serum Glutamate Oxaloacetate Transaminase (SGOT) and Serum Glutamate Pyruvate Transaminase (SGPT) levels. Increased SGPT and SGOT levels are indicators of liver necrosis. Objective: This study aimed to prove the association between SII and ferritin with SGPT and SGOT levels in thalassemia major patients. Methods: An observational analysis with a cross-sectional approach was adopted to analyze the medical records of pediatric patients at the Kasuari Clinic of Dr. Kariadi Hospital Semarang from September to October 2023. SII value and ferritin level were the independent variables, while SGOT and SGPT were dependent. Data were collected and analyzed univariately for characteristic description and bivariately using the Spearman test. Results: The median SII value, ferritin level, SGPT level, and SGOT level in thalassemia major patients were 451.73/L, 2097.30 ng/mL, 20.00 U/L, and 40.00 U/L. The results showed there was a moderately significant association between SII values and SGOT levels (p=0.010, r=-0.457) as well as ferritin and SGPT (p=007, r=0.475). There was no significant association between SII values and SGPT levels, as shown by a p-value of 0.122. Similarly, there was no association between ferritin and SGOT levels (p=0.088). Conclusion: A moderately significant association was found between SII values and SGOT levels, as well as ferritin levels and SGPT levels in thalassemia major patients.